Glycosylation of FGFR4 in cholangiocarcinoma regulates receptor processing and cancer signaling. Issue 3 (4th January 2022) - Phillips, Andrew J.; Lobl, Marissa B.; Hafeji, Yamnah A.; Safranek, Hannah R.; Mohr, Ashley M.; Mott, Justin L.
Abstract: Recent advances in targeted treatment for cholangiocarcinoma have focused on fibroblast growth factor (FGF) signaling. There are four receptor tyrosine kinases that respond to FGFs, and posttranslational processing has been demonstrated for each FGF receptor. Here, we investigated the role of N‐linked glycosylation on the processing and function of FGFR4. We altered glycosylation through enzymatic deglycosylation, small molecule inhibition of glycosyltransferases, or through site‐directed mutagenesis of selected asparagine residues in FGFR4. Signaling was tested through caspase activation, migration, and subcellular localization of FGFR4. Our data demonstrate that FGFR4 has multiple glycoforms, with predominant bands relating to the full‐length receptor that has a high mannose‐ or hybrid‐type form and a complex‐type glycan form. We further identified a set of faster migrating FGFR4 bands that correspond to the intracellular kinase domain, termed FGFR4 intracellular domain (R4‐ICD). These glycoforms and R4‐ICD were detected in human cholangiocarcinoma tumor samples, where R4‐ICD was predominant. Removal of glycans in intact cells by enzymatic deglycosylation resulted in increased processing to R4‐ICD. Inhibition of glycosylation using NGI‐1, an oligosaccharyltransferase inhibitor, reduced both high mannose‐ or hybrid‐ and complex‐type glycan forms of FGFR4, increased processing and sensitized to apoptosis. Mutation of Asn‐112, Asn‐258, Asn‐290, or Asn‐311 to glutamine modestly reduced apoptosis resistance, while mutation of Asn‐322 or simultaneous mutation of the other four asparagine residues caused a loss of cytoprotection by FGFR4. None of the glycomutants altered the migration of cancer cells. Finally, mutation of Asn‐112 caused a partial localization of FGFR4 to the Golgi. Overall, preventing glycosylation at individual residues reduced the cell survival function of FGFR4 and receptor glycosylation may regulate access to an extracellular protease or proteolytic susceptibility of FGFR4.